2016
DOI: 10.1177/0093854816651905
|View full text |Cite
|
Sign up to set email alerts
|

Desistance from Crime and Identity

Abstract: Theories of desistance from crime have emphasized social processes like involvement in adult social bonds or prosocial social relationships to the deliberate neglect of individual subjective processes such as one's identity. More recent theories, however, have stressed the role of identity and human agency in the desistance process. An important set of questions is whether identity theory adds anything to existing theories, and whether there is empirical evidence to suggest that such subjective processes are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 51 publications
(100 reference statements)
3
37
0
2
Order By: Relevance
“…Finally, a third group of desistance explanations highlight the fact that individuals experience a cognitive or identity transformation (Giordano, Cernkovich, & Rudolph, 2002;Maruna, 2001;Walker et al, 2013). This change in identity may be the result of learning new roles and definitions of behavior (Giordano et al, 2002;Paternoster et al, 2016), the acquisition of a new prosocial self-concept (Farrall & Maruna, 2004;Maruna, 2001Maruna, , 2004Maruna & Roy, 2007), or an increased perception of the benefits derived from leading a prosocial life (Doekhie et al, 2017;Paternoster & Bushway, 2009;Paternoster et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a third group of desistance explanations highlight the fact that individuals experience a cognitive or identity transformation (Giordano, Cernkovich, & Rudolph, 2002;Maruna, 2001;Walker et al, 2013). This change in identity may be the result of learning new roles and definitions of behavior (Giordano et al, 2002;Paternoster et al, 2016), the acquisition of a new prosocial self-concept (Farrall & Maruna, 2004;Maruna, 2001Maruna, , 2004Maruna & Roy, 2007), or an increased perception of the benefits derived from leading a prosocial life (Doekhie et al, 2017;Paternoster & Bushway, 2009;Paternoster et al, 2016).…”
mentioning
confidence: 99%
“…It has been highlighted that the expression of a positive outlook in early stages of imprisonment would favor inmates' future desistance from crime (Apel, 2013;Giordano et al, 2002;Laub & Sampson, 2001;Maruna, 2001;Paternoster & Bushway, 2009). Shapland and Bottoms (2011) have also suggested that for offenders to improve their self-perception they must begin by showing in early stages of imprisonment an initial desire to change.…”
mentioning
confidence: 99%
“…Similarly, suggest that, while it is unclear how RJ contributes to rehabilitation, it has a more obvious role in relation to desistance. One part of desistance involves developing an identity as a moral person (i.e., non-offender) (Maruna, 2001;Paternoster et al, 2016;Rocque et al, 2016). Engagement in RJ provides an opportunity for an individual to develop a desistance identity.…”
Section: Restoring People Responsible For Crimementioning
confidence: 99%
“…Explanatory emphases have been placed on the supervisory impact felt upon entry into prosocial institutions and adult social bonds [69,103], the short durational prevalence of normative anti-social adolescent behavior [80], and evidence that the precipitous declines in offending following adolescence are attributed to rational responses to changes in the perceived costs and benefits of crime [92]. Although an interdisciplinary research focus on the age-crime curve has developed in very meaningful ways, most of the inquiry has explored men's offending patterns or mixedgender samples of adolescents and younger adults.…”
Section: Introductionmentioning
confidence: 99%